Beyond Nostalgia: Formula and Novelty in Old English Literature. (January 2014) - Sharma, Manish
<x content-type="archive" xml:space="preserve">Abstract</x> Oral-formulaic theory has had an immense impact on the way we read and interpret Old English literature. Formulaic theory, however, can only think in terms of the repetition of "discrete, " pre-existent, and isolable units. But for Henri Bergson, the real is continuous and creative, not discrete and immobile. Following Bergson's account of "continuous multiplicity" in Creative Evolution and drawing on Gilles Deleuze and Félix Guattari's extension of Bergson's thought in A Thousand Plateaus, I propose a higher order theory of Old English literary production that acknowledges its traditionalism and formulaicity, even as it attempts to conceive of the corpus in terms of novelty, originality, and experimentation. The wager is that vitalist philosophical models will allow readers to conceive of Old English literature beyond a nostalgic insistence on the return of the same.